Implementation of Insecticide for Fogging and Larvicidation in Dengue Fever Control and Its Impact on Vector Resistance in Banjarmasin City: A Qualitative Analysis - Juhairiyah; Muhammad Rasyid Ridha; Indriyati, Liestiana; Yudhastuti, Ririh; Triwibowo Ambar Garjito; Muhammad Choirul Hidajat; Wahyu Pudji Nugraheni; Nurul Hidayah; Isnawati; Babucarr Jassey (Universitas Airlangga, 2025)
Introduction: Dengue remains a major public health concern in Indonesia, including Banjarmasin. Insecticide-based interventions, such as fogging and larviciding, are key components of dengue vector control. However, improper implementation can lead to insecticide resistance, reducing program effectiveness. Methods: This qualitative study aimed to evaluate the implementation of insecticide use in the dengue control program in Banjarmasin. Data were collected through in-depth interviews, observations, and document reviews at national, provincial, and municipal levels. A total of 60 informants were purposively selected, including stakeholders from the Ministry of Health, provincial and city health offices, pharmaceutical warehouses, community health centers, sub-districts, and urban villages. Data were analyzed using a deductive Input-Process-Output (IPO) model and inductive gap analysis. Triangulation was applied to ensure data validity. Results and Discussion: The study revealed that the absence of national and local insecticide resistance mapping hinders the implementation of insecticide rotation policies. Other challenges include a shortage of trained entomology personnel, limited training, weak intersectoral coordination, and poor dissemination of vector control regulations, particularly regarding fogging procedures. Moreover, unsupervised community-led fogging often deviates from standard operating procedures. Conclusion: Strengthening human resource capacity, improving insecticide distribution planning based on resistance data, and enhancing regulatory enforcement are critical to improving program effectiveness. Promoting community-based approaches is also essential to support sustainable and responsive dengue vector control strategies.